Transportation, sale and consumption of food in Antioquia (IV-V century) - Ventura da Silva, Gilvan; Silva, Érica Cristhyane Morais da (Romanitas - Revista de Estudos Grecolatinos, 2024)
In this article, we intend to shed light on the transport, sell and consumption of food kinds in Antioch, the metropolis of the Syrian-Coele province, in the fourth and fifth centuries, through the examination of the speeches by Libanius, one of the most important ancient orators who was born in the city.  Moreover, we also examine the so-called Mosaic of Megalopsychia, a polychromatic opus tessellatum found in Yakto, a district of Antioch, by the archaeologists who took part in the excavations campaigns of the town and its vicinity between 1932 and 1939.
Keywords: Late Antiquity; Urban Trade; Food; Antioch